The 'Civilising Mission' of Portuguese Colonialism, 1870-1930 - Jerónimo, Miguel Bandeira. author. aut Link
VIII, 269 p.
Keywords: This book provides an historical, critical analysis of the doctrine of 'civilising mission' in Portuguese colonialism in the crucial period from 1870 to 1930. Exploring international contexts and transnational connections, this 'civilising mission' is analysed and assessed by examining the employment and distribution of African manpower.